DEVELOPMENT OF ZSM-5 ZEOLITE CATALYST FOR PHENOL REMOVAL USING CATALYTIC OZONATION TECHNOLOGY - Dharma Utama, Alvin
Phenol waste is one of the organic compounds and can be found in petroleum, coal, petrochemical, pharmaceutical, plastic, paint, and paper industries. Phenol waste is classified as B3 waste (Hazardous and Toxic Materials) because of its toxicity. One of the effective methods to treat phenol waste is using ozonation technique. Ozone can oxidize phenolic compounds because it is highly reactive and also can remove color and odor. However, the single ozonation process has a low efficiency for degrading pollutants due to the low solubility of ozone in water and organic compounds cannot be oxidized quickly. In order to improve the degradation efficiency of organic compounds, catalytic ozonation technology was developed. The presence of a catalyst can increase the rate of ozone decomposition and produce active free radicals (hydroxyl radicals) which can increase the degradation and mineralization of organic pollutants. Of several types of catalysts that have been developed for catalytic ozonation technology, zeolite has been widely used as a catalyst in the catalytic ozonation process to degrade various organic chemical compounds including phenol. The purpose of this research was to develop a zeolite-based catalyst to degrade phenol from wastewater using catalytic ozonation technology. Zeolite ZSM-5 was chosen as the catalyst used in this study. Zeolite ZSM-5 will be synthesized using a tubular reactor with a batch system. The zeolite synthesis in a tubular reactor was proven to be used for the synthesis of ZSM-5 zeolite (reproducible). The optimum condition for the synthesis of ZSM-5 zeolite was obtained for 1 hour at a temperature of 210 oC with a yield of ±25%. The characteristics of the synthesized ZSM-5 zeolite had high crystallinity (>80%) with composition of Si/Al 46-55. The form of synthesized ZSM-5 crystal was hexagonal aggregates and non-uniform, with surface area was 236-307 m2/g. The used of ZSM-5 as catalyst could increase the average phenol degradation by 76.25%. Modification of the catalyst ZSM5-5h to HZSM5-5h could increase the zeolite acidity by 49%, but reduce the degradation of phenol by 10%. The highest phenol degradation was obtained 88.66% using ZSM5-5h catalyst with 90% ozone concentration.